Construção e aplicação de uma coleção de jogos didáticos para ensino de física no ensino médio - Uyeda, Fabiana Aparecida Santos (2018)
The specialized literature indicates that one of the obstacles to the teaching of Physics in High School is the excessively focused approaches in lectures with little capacity to engage students in the learning process. On the other hand, the literature indicates that it is important that physics teachers seek approaches in which students have the opportunity for greater interaction, engagement in activities, being the protagonists of the lesson and learning. Within this perspective, for example, the so-called active learning approaches, research teaching, as well as activities that can be playful and that guarantee the protagonism of the student have been highlighted. Based on the concept of play activity with didactic purposes, our main objective in this work was to investigate from a case study the main elements (parameters) for the organization of processes involving groups of students in game creation, with relevant content, as a learning strategy of Physics. For this, opportunities were created for the students to construct games, involving content of the CBC (Basic Common Contents) of Physics. From successive rounds these games were perfected and made available as a resource for teaching and evaluation in Physics. As main product, we were able to obtain a set of parameters or essential elements necessary to favor the achievement of didactic purposes in games in Physics teaching and a collection of tested suggestions so that teachers can adapt this experience to their conditions and needs in didactic activities.